DIPG-70. CLINICAL, RADIOLOGICAL, PATHOLOGICAL AND MOLECULAR CHARACTERISTICS OF CHILDREN <3 YEARS WITH DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG): A REPORT FROM THE INTERNATIONAL DIPG REGISTRY. Issue 2 (22nd June 2018) - Bartlett, Allison; Cochrane, Anne; Lane, Adam; Yanez-Escorza, Nancy; Chaney, Brooklyn; Doughman, Renee; DeWire-Schottmiller, Mariko; Goldman, Stewart; Warren, Kathy; Bandopadhayay, Pratiti; Foreman, Nicholas; Shih, Chie-Schin; et al.
Abstract: BACKGROUND: Children <3 years with DIPG are reported to have a higher rate of long-term survival (LTS, overall survival (OS) ≥24 months). In patients <3 years with centrally confirmed DIPG, we compared clinical, radiological, histological and molecular characteristics between LTS versus short-term survivors (STS <24 months). METHODS: Data from children <3 years on the International DIPG Registry (IDIPGR) were analyzed. RESULTS: Among 782 DIPG patients, 53 were <3 years; 13 were excluded (3 without imaging, 10 "unlikely DIPG" on central review). Of the remaining 39 with at least 24-month follow-up, 10 (26%) were LTS. Among 29 patients who received therapy, 9 (31%) were LTS; median OS was 16 months (range: 2–123+ months); 27/29 (93%) received radiotherapy, including all treated LTS (9/9). Median OS among patients who did not receive therapy was 2 months, but included one LTS (37 months). LTS presented with longer symptom duration (p=0.004); tumor size, ring enhancement, necrosis and extra-pontine extension on MRI did not reach significance. Biopsy and/or autopsy was performed in 43% of patients; 50% had H3K27 mutations. Whole genome sequencing and RNA sequencing are being conducted to correlate key parameters (e.g. NTRK fusions, P53 mutations, H3K27 mutations, ACVR1) with outcome. CONCLUSION: In the largest series reported to date, children <3 years with centrally confirmed DIPG demonstrated a significantly higher rate of LTS and improved median OS. LTS were more likely to have longer duration of symptoms. Only 50% had H3K27 mutations. Final genomic analyses will be presented, and may reveal predictors of improved outcome.